An evaluation of the in-patient feedback services in a tertiary care hospital of Northern India - Samant, Shweta; Saini, Ravinder Singh (International Journal Of Community Medicine And Public Health, 2019)
Background: Patient satisfaction is an important indicator of the quality of services provided by any healthcare organization and directly or indirectly affects patient retention, legal issues, revenues, reputation and success of a healthcare organization. Patient’s feedback about the clinical as well as non-clinical services can be recorded for gap analysis and improvement of services. Methods: The cross-sectional study was carried out in a large tertiary care hospital in North India from May 2012 to December 2012. A pre-tested internally developed questionnaire was used to collect the data. Results: It was observed that the average satisfaction score was relatively high for the criteria like doctor’s counselling, attitude of nurse and availability and behaviour of attendant. The average scores for medical and nursing care (clinical services) provided in wards were high (70-74% satisfaction). However, approximately 45% and 50% patients were dissatisfied with the housekeeping and dietary services respectively. This resulted in a dip in the overall impression of the hospital services to 68%. Conclusions: The percentage of patients satisfied with the overall services (clinical and non-clinical) of the hospital is only 68% which goes on to prove that the patients’ perception of quality is changing with the times and non-clinical areas like housekeeping, dietary, billing, security services are becoming as important as clinical care services that are provided by hospitals.